ANALISIS FAKTOR RISIKO TERJADINYA SISA MAKANAN PADA PASIEN JIWA DI RUMAH SAKIT JIWA PROF. DR. V. L RATUMBUYSANG MANADO - Rudolf Boyke Purba; Mirna Kawulusan; Resmin Sangkide (POLTEKKES KEMENKES MANADO, 2014)
The nutrition service of the hospital is a community nutrition needs fulfillment activities toimproving health as well as to correct abnormalities in the metabolism of the body in theframework of preventive efforts (prevention), promotif, curative and rehabilitative.The patientreceived power of food served can be seen from the rest of the food. The success of anorganization can be assessed from the food there is absence of leftovers, so leftovers can beused as indicators for evaluating the activities of the Organization of the hospital food.Thepurpose of the research: find out the factors of occurrence of leftovers mental patients treated inpsychiatric hospitals, Prof. Dr. v. l. Ratumbuysang Manado. Types of observational analyticstudy.Research conducted in July 2014 in a mental hospital, Prof. Dr. v. l. Ratumbuysang.Populations in the study are all patients with psychiatric disorders and sample as many as 67people and sampling based on purposive sampling.Data collected data record medic,leftovers.Data analysis to answer hypotheses using Test Chi Square statistical tests. The resultis that like to eat spicy and fried-fried foods (74.6%) don't eat spicy and fried-fried foods (25.4%),the patient's psychic soul belongs to the continental level (6%), the level was as much as (94percent). Organization of the food in the hospital who are satisfied with the appearance of food(97 percent), taste (94 percent). Leftovers in patients who successfully found on fruit are (were95.5 percent). Conclusion: there is a relationship of eating habits with the rest of the food animalside (p = 0.03), There is no relationship with the rest of the rice eating habits (p = 0,52),vegetable side dish (p = 0.48), vegetable (p = 0.42), fruit (p = 0.75), there was no relationshippsychic with the remaining rice (p = 0,52), animal side (p = 0.27), vegetable side dish (p = 0.32),vegetable (p = 0.16), fruit (p = 0,83), there was no relationship with the food the food'sappearance at Rice (p = 0.21, animal side (p = 0.53), vegetable side dish (p = 0.42), vegetable(p = 0,62), fruit (p = 0.92). The taste of food, rice (p = 0.63), animal side (p = 0.63), animal side(p = 0,71), vegetable side dish (p = 0.32), vegetable (p = 0.16), fruit (p = 0,83)